The use of health care services by Pacific Islands people in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Tofi, Tavita Aofia (Massey University, 1996)
In a replication of Wolinsky and Johnson's (1991) study, data from 53 Pacific Islanders were used to examine relationships hypothesised in Andersen's behavioural model of health services utilisation, using additional measures of predisposing factors, enabling factors, need factors and the use of health care services. The findings revealed that the inclusion of extra measures did not improve the predictive utility of the model on two measures of health services use. The need variable of upperbody limitations proved to be a significant predictor of the use of other health professionals consulted by respondents. For other measures of services use, analysis of variance showed that these were related to need variables only. For utilisation patterns amongst the group, there were some evidence of problems with access to health services use through issues of accommodation, acceptability, and lack of familial resources. Bivariate analyses also showed gender differences in a number of health behaviours amongst this group. These findings are discussed with implications provided for future research.
Keywords: Medical care; Pacific Islanders; Utilisation; Health and hygiene; Mental health; New Zealand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Health and medical services in society